Analisis Feedback Pengguna Aplikasi Shopee Menggunakan Distribusi Proporsi dan Teknologi Informasi - Dora Alvionita; Lidiya; Jadiaman Parhusip (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
This research aims to analyze Shopee application user feedback using Google Colab-based information technology and a proportion distribution approach. The method used includes a Multinomial Naïve Bayes-based classification technique to categorize sentiment into positive and negative. The research results show that the model accuracy level is 90.84% ​​with an average precision for the positive and negative categories of 0.93 and 0.78 respectively. The statistical test produces a T-statistic value of 2759.50 with a p-value of 0.0, which shows significance in the difference in the distribution of positive and negative reviews.